PENGARUH WORK CLIMATE, SELF-EFFICACY DAN JOB INSECURITY TERHADAP KINERJA KARYAWAN PADA PT AVO INNOVATION & TECHNOLOGY DI YOGYAKARTA - Ma’rifah, Ririn; Darmawan, Surya (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
The objective of this study is to analyze the relationship between Work Climate, Self-Efficacy, and Job insecurity on employee performance. This research employs a purposive sampling technique, with a total of 176 respondents (87 men and 89 women). The population in this study consists of employees at PT Avo Innovation and Technology. Primary data for this study were collected using a questionnaire distributed via Google Forms, which has been tested for validity and reliability. In this study, SmartPLS 4.0 software was used for descriptive statistical, outer model and inner model analysis. The results of this study indicate that work climate has a positive and significant effect on employee performance. Self-Efficacy also has a positive and significant effect on employee performance. Similarly, Job insecurity has a positive and significant effect on employee performance. Work climate, self-efficacy, and job insecurity simultaneously have a positive effect on employee performance.